Bus stand lamp using piezoelectric energy - Mohd Nasir, Mohamad Na'im; Aziz, Muhammad Nasiruddin; Bohari, Zul Hasrizal; Jaafar, Hazriq Izzuan; Jali, Mohd Hafiz; Nor, Mohd Khanapiah (2014)
The development of piezoelectric energy harvester has rapidly becoming an attractive research in these few years mainly due to the largely use of semiconductor in power supply technology. Harvesting ambient vibration energy using piezoelectric element has become an interesting topic since the technology is using the free energy source, which can reduce a significant value in cost development. The prototype of bus stand lamp using piezoelectric energy was developed to show the concept of the harvester system. The objective of this product is to overcome the lacking lighting system problem for bus stand at rural place. By using the free energy source, which is gain from the people walking across this area, the piezoelectric disc was placed on the floor whereby the location of the piezoelectric disc is determined based on the maximum harvesting output power when people step on it. Power that harvested will then be stored in the super capacitor or battery before delivered to the load. The light emitting diode (LED) is used as the supply of the light to the bus stand since the energy efficiency of LED is higher compared to the traditional lighting. Two experiments were conducted to determine the maximum output of piezoelectric harvesting base which from the experimental results, it shows that a significant output voltage and current of 0.372A and 0.421A respectively is successfully generated which then can be use to charge the battery.